Review of Pandara DeLong & Freytag (Insecta: Hemiptera: Cicadellidae: Gyponini), raised to generic status, including three new species and an identification key - Silva, Marcelo Peixoto Gomes Da; Gonçalves, Clayton Corrêa; Takiya, Daniela Maeda (Zootaxa, 2024)
The monotypic subgenus Pandara DeLong & Freytag, 1972 of Gyponana Ball, 1920 is reviewed, and proposed to be raised to generic rank, with new diagnostic characters provided. The type-species Gyponana (P.) eleganta DeLong & Freytag, 1972 described from Santa Cruz, Bolivia is redescribed. In addition, three new species for the genus are described and illustrated: Pandara inca sp. nov. from Peru, Pandara indivisa sp. nov. from Peru and Bolivia, and Pandara parallela sp. nov. from Brazil and French Guiana. The female terminalia of a representative of this genus is described for the first time. A species identification key for males and a distribution map for the four known species are provided.